Use Of Instagram As A Promotional Media For Buper Segorogunung Perum Perhutani Kph Surakarta Kph Surakarta - Aldo Hizbullah Alfariz; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2025)
Segorogunung Camping Ground is one of the ecotourism sites belonging to KPH Surakarta which is managed by Pokdarwis Argo Kuncoro. The ecotourism manager uses one of the social media platforms, namely Instagram, as a promotional medium. However, the Buper Segorogunung Instagram account is less active in promotional activities. This can be seen from the inconsistent and less interesting uploaded content. Therefore, the author will discuss how to use Instagram as a promotional medium for the development of Buper Segorogunung KPH Surakarta. The aim of this research is to determine the implementation of digital marketing strategies through Instagram social media at the Segorognung Campground tourist attraction. This research uses qualitative research methods to analyze the differences in marketing strategies implemented by Buper Segorogunung managers when using the Instagram platform as a promotional tool. Data was collected through in-depth interviews with managers, direct observation of official Instagram accounts, and documentary studies of published content. According to the author, an effective digital marketing strategy includes using attractive visual content, actively interacting with users, and using Instagram features such as Stories and Reels. However, the results of observations and implementation during the internship show that Buper Segorogunung's Instagram still tends to be less active and less consistent in uploading content, and also rarely updates stories (Instastory). This research is expected to provide insight into optimizing social media as a digital marketing tool for tourism managers, especially in the natural tourism sector.